2015
DOI: 10.1111/and.12498
|View full text |Cite
|
Sign up to set email alerts
|

Neutral alpha-1,4-glucosidase and fructose levels contribute to discriminating obstructive and nonobstructive azoospermia in Chinese men with azoospermia

Abstract: Nowadays, whether neutral alpha-1,4-glucosidase (NAG) and fructose levels are contributed to discriminating obstructive and nonobstructive azoospermia in Chinese azoospermic patients remains unclear. In this study, we retrospectively analysed the levels of NAG and fructose in 229 patients with obstructive azoospermia and 415 patients with nonobstructive azoospermia from three different medical central. Results indicated that NAG and fructose levels in patients with nonobstructive azoospermia were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The reason for higher levels of fructose in seminal plasma of low fertile and infertile groups might be attributed to inefficiency or inability of spermatozoa to utilize free fructose in the seminal plasma (Lei et al, 2015). The ability of spermatozoa to utilize the free fructose is under the regulation of glycolytic enzymes and any deficiency or absence of these proteins/enzymes affect Figure 5 The sperm proteins from fertile, low fertile, and infertile were profiled using 2D gel electrophoresis.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for higher levels of fructose in seminal plasma of low fertile and infertile groups might be attributed to inefficiency or inability of spermatozoa to utilize free fructose in the seminal plasma (Lei et al, 2015). The ability of spermatozoa to utilize the free fructose is under the regulation of glycolytic enzymes and any deficiency or absence of these proteins/enzymes affect Figure 5 The sperm proteins from fertile, low fertile, and infertile were profiled using 2D gel electrophoresis.…”
Section: Discussionmentioning
confidence: 99%
“…Epididymis is an important place for sperm capacitation before fertilisation, which plays a key role in sperm maturation and motility (Moore, ; Pena, Sanchez, Vasquez, Castillo, & Miska, ). NAG is exclusively generated in epididymis, which is regarded as a marker to evaluate the function of epididymis (Lei et al., ; Levrant et al., ). Said et al.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the cut‐off value of NAG defined by World Health Organization () was not most sensitive and specific in Chinese patients (Lei et al., ). So, we supposed that NAG levels in different races from different country might be variable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of fructose and neutral alpha glucosidase for discriminating obstructive and non obstructive azoospermia are well documented. 4,5 The methods for semen biochemical marker of seminal plasma have been develop from manual, semi-automatic, and fully automatic. The automatic method has several advantages such as simple reagent preparation, smaller amount reagents needed for each test, few errors, reduction manpower, simple calibration, and quality control procedure.…”
Section: Automatic Assessment Of Biochemical Marker Of Seminal Plasmamentioning
confidence: 99%